Creativity, culture, and development - Tan, Ai-Girl; Perleth, Christoph (Creativity in the Twenty First Century, 2015)
This volume presents a collection of writings on the relations among creativity, culture and development. The editors invited "like-minded" researchers of creativity from around the world to share their respective notions of creativity. Given that human creativity is a potential that can and should be nurtured in the course of lifespan development and across all cultural backgrounds, the volume emphasizes the importance of promoting creativity in all cultures and through societal-educational opportunities, and offers a venue for the authors to make conceptual, empirical and practical inquiries into the relations among creativity, development and culture. The authors represent a varied "mix" of contemporary and emerging creativity researchers who use different methodologies to investigate the importance of culture in creativity development, and the reciprocal role of developing creativity and cultural enrichment. The volume represents an attempt on the part of the editors and the authors to broaden our current understanding of creativity in the contexts of human and cultural development, and in so doing to enhance our understanding of creativity, culture and development in the contexts of flourishing human and societal activities. As the first volume in a book series on "Creativity in the Twenty-First Century", the book invites readers and researchers to engage in future interdisciplinary and intercultural discourses and dialogues on the importance of creativity for human and cultural development.